A cancellation method of additive external noise and state dependent noise in sound environment systems. (21st November 2014) - Ikuta, Akira; Siddique, Nazmul H.
In the actual situation of sound environment systems, the observed data often contain several fluctuating noises. Therefore, it is necessary to estimate the specific signal based on the observed data by introducing a noise cancellation method. In this study, a sound environment system considering both noises of the external noise based on the additive property of energy variable and the internal noise dependent on the state variable is first paid our attention. Next, a noise cancellation method to estimate recursively the specific signal is derived on the basis of Bayes' theorem in an expansion series form suitable to a recursive signal processing. Finally, the validity of the proposed method is experimentally confirmed by applying it to the actual data observed in real sound environment.